Surrendering to reality: a qualitative study on the shift in PhD pursuit intentions among Chinese humanities and social sciences master’s students - Feng, Yang; Zhong, Zhiyong (Frontiers in Education, 2025)
Previous research has extensively explored the motivations for pursuing a PhD, aiming to answer the question of “why pursue a doctorate.” However, it has largely overlooked the group that ultimately abandons this pursuit. This paper takes rational choice theory as the analytical framework, and through in-depth interviews with 25 humanities and social sciences academic master’s students, it explores the dynamic process and the complex factors behind the changes in the choice of, with the aim of answering the question of “Why do master’s students who initially have the willingness to pursue a doctoral degree ultimately give up?.” The study reveals that their decision-making process undergoes three distinct stages. That is, the stage of motivation formation based on social rationality, the stage of resource allocation based on conditional integration, and the stage of decision-making and trade-off based on survival rationality and economic rationality. This dynamic process and its decision-making mechanism are deeply influenced by individuals’ social class, supporting the effectively maintained inequality theory. The conclusions offer important implications for refining graduate education policies and understanding the relationship between doctoral degree attainment and family background.